Global clinical trials on stem cell therapy for autoimmune diseases: trends and future directions - Yanhao Chen; Xiang Li; Jiao Zhang; Jiaqi Peng; Fugang Huang; Jie Bao; Yongsheng Fan; Shuo Huang (Frontiers in Immunology)
BackgroundAutoimmune diseases, such as Crohn’s disease (CD) and systemic lupus erythematosus (SLE), lead to progressive multi-organ damage due to immune dysregulation and chronic inflammation. Current therapies lack efficacy and safety, often failing to sustain remission. Stem cell therapy has emerged as a promising approach for immune modulation and tissue repair. This study analyzes clinical trial trends and challenges of stem cell therapy in autoimmune diseases.MethodsClinical trial data (2006–2025) were extracted from Trialtrove. Strict inclusion criteria were applied, restricting the analysis to interventional trials while excluding observational studies, non-autoimmune disease trials, and records with incomplete information. Descriptive statistics were used to analyze trial phases, disease types, geographic distribution, funding sources, therapeutic mechanisms, and stem cell sources, followed by a comparative evaluation of therapeutic efficacy, combination strategies, and safety profiles across autoimmune indications.ResultsOf the 1,511 global trials, 244 were included after screening and cross-referencing. Most trials (83.6%) were in Phase I-II. CD (n=85), SLE (n=36), and scleroderma (n=32) were the most studied. The U.S. and China led in trial numbers. Academic institutions funded 49.2% of trials. Key therapeutic strategies included immune modulation, tissue repair via growth factors, and anti-infection/anti-proliferative effects. Disease-specific variations were noted in cell sources and administration routes.ConclusionStem cell therapy holds substantial promise for autoimmune disease treatment. Future efforts should prioritize technological innovation, international collaboration, and precision medicine to address current challenges and advance clinical translation.